Immunization of Zika virus envelope protein domain III induces specific and neutralizing immune responses against Zika virus. Issue 33 (24th July 2017) - Yang, Ming; Dent, Matthew; Lai, Huafang; Sun, Haiyan; Chen, Qiang
Abstract: In this study, we described the generation and immunogenicity of the Zika Virus (ZIKV) envelope protein (E) domain III (DIII) as a protein subunit vaccine candidate. ZIKV EDIII (zEDIII) was rapidly produced in E. coli in inclusion bodies. ZIKV EDIII was solubilized, refolded and purified to >95% homogeneity with a one-step Ni 2+ affinity chromatography process. Further analysis revealed that zEDIII was refolded properly and demonstrated specific binding to an anti-zEDIII monoclonal antibody that recognizes a zEDIII conformational epitope. Subcutaneous immunization of mice with 25 and 50 μg of zEDIII was performed over a period of 11 weeks. zEDIII evoked ZIKV-specific and neutralizing antibody response with titers that exceed the threshold that correlates with protective immunity against ZIKV. The antigen-specific IgG isotypes were predominantly IgG1 and splenocyte cultures from immunized mice secreted IFN-gamma, IL-4 and IL-6. Notably, zEDIII-elicited antibodies did not enhance the infection of dengue virus in Fc gamma receptor (FcγR)-expressing cells. This study provided a proof of principle for the further development of recombinant protein-based subunit vaccines against ZIKV.